Repetition as Trapped Emotion in Tennessee Williams’s the Glass Menagerie - Kusovac, Olivera; Pralas, Jelena (Studia Anglica Posnaniensia, 2017)
Repetition as a linguistic and stylistic device extensively used in Tennessee Williams’s plays has been noticed by many. At the same time, more psychologically-inclined scholars have frequently drawn parallels between Williams’s plays and his own experiences and emotional conflicts. In an attempt to combine the two perspectives, this article will explore the function of repetitions as indicators of trapped emotions in Williams’s celebrated and award-winning play The Glass Menagerie. Starting from the stylistic theoretical background, but at the same time taking into account the psychological insights into the link between Williams’s life and work through some basic concepts of Freud and Lacan, an attempt will be made to demonstrate that in this play linguistic repetition appears as an obsessive expression of the characters’ emotions as well as those of the dramatist himself, making him repeat and relive both his experiences and his emotions. The authors will first introduce the concept and functions of repetition as a linguistic and stylistic device and then explore its representative instances in individual characters and their meanings, ending with the parallels which can be drawn between the characters’ and the dramatist’s own experiences and emotions expressed or intensified through repetitions.